2021
DOI: 10.4012/dmj.2019-300
|View full text |Cite
|
Sign up to set email alerts
|

Shear bond strength of veneering composite to high performance polymers

Abstract: High performance polymers like PEEK (polyetheretherketone) and FRC (fiberreinforced composite) could substitute metallic alloys for removable partial dentures. However, these polymers require aesthetic veneering. This study was to determine the bond strength to direct composite. Specimens made of PEEK and FRC were produced and air-abraded (50 μm aluminum-oxide). Specimens were allocated to four experimental groups: Luxatemp Glaze & Bond, Scotchbond Universal, SR Nexco Connect and iBond Universal. Specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
1
7
1
Order By: Relevance
“…Depending on the aging time in PEEK specimens, SBS values of 8.75-14 MPa were obtained. The SBS values herein are less than those obtained in a study reported by Bunz et al (21); the authors did not indicate the waiting time between the pre-treatment, conditioning, and veneering stages for application to the PEEK surface. Composite resin and adhesive material must be applied immediately as the PEEK surface properties can change within a few minutes after air-abrasion pre-treatment.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Depending on the aging time in PEEK specimens, SBS values of 8.75-14 MPa were obtained. The SBS values herein are less than those obtained in a study reported by Bunz et al (21); the authors did not indicate the waiting time between the pre-treatment, conditioning, and veneering stages for application to the PEEK surface. Composite resin and adhesive material must be applied immediately as the PEEK surface properties can change within a few minutes after air-abrasion pre-treatment.…”
Section: Discussioncontrasting
confidence: 89%
“…Bunz et al investigated the effect of aging on SBS values by the application of a universal adhesive to PEEK specimens for surface treatment by airborneparticle abrasion using 50-µm Al2O3 (21). Depending on the aging time in PEEK specimens, SBS values of 8.75-14 MPa were obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsuka et al tested PEEK bonding with resin-based luting materials including Panavia V5 (0.8 ± 0.4 MPa), RelyX Ultimate Resin Cement (5.2 ± 1.3 MPa), G-CEM Link Force (3.7 ± 1.4 MPa), and Super-Bond C&B (8.2 ± 1.3 MPa) and found that SBS failed to reach 10 MPa with any of them and that the majority of the failure modes resulted from decementation [30]. This finding was consistent with those reported by other groups [95,105].…”
Section: Adhesive Systemssupporting
confidence: 92%
“…Specimens were stored in a remineralization solution (Aqua bidest1 mol Potassium chloride, 150 mmol Calcium chloride, 90 mmol Potassium dihydrogen phosphate) as published recently [ 28 ]. The specimens were divided into two subgroups of short- and long-term artificial aging.…”
Section: Methodsmentioning
confidence: 99%